2017
DOI: 10.3390/ijerph14121599
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Performance Evaluation for Hydrological and Nutrients Simulation Using the Hydrological Simulation Program–Fortran in a Mesoscale Monsoon Watershed, China

Abstract: The Hydrological Simulation Program–Fortran (HSPF) is a hydrological and water quality computer model that was developed by the United States Environmental Protection Agency. Comprehensive performance evaluations were carried out for hydrological and nutrient simulation using the HSPF model in the Xitiaoxi watershed in China. Streamflow simulation was calibrated from 1 January 2002 to 31 December 2007 and then validated from 1 January 2008 to 31 December 2010 using daily observed data, and nutrient simulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 70 publications
(93 reference statements)
1
5
0
Order By: Relevance
“…This explanation is supported by the study conducted by Li et.al. [35], who used hydrological and water quality model, HSPF, where a similar trend with this study between the model simulated and observed flow was observed. The spatial location of rain meters and the heterogeneity among rainfall stations could also determine the deviation.…”
Section: Flow Simulation and Pollutants Flux In Larsupporting
confidence: 83%
See 1 more Smart Citation
“…This explanation is supported by the study conducted by Li et.al. [35], who used hydrological and water quality model, HSPF, where a similar trend with this study between the model simulated and observed flow was observed. The spatial location of rain meters and the heterogeneity among rainfall stations could also determine the deviation.…”
Section: Flow Simulation and Pollutants Flux In Larsupporting
confidence: 83%
“…Though the estimation of point source load is relatively easy, it is challenging to quantify diffuse source loads, specifically in developing countries, where the estimation is often based on simple empirical equations with limited hydro-meteorological and water quality data. To fill such gaps, many watershed models have been developed and studies were conducted to determine pollutant loads from diffuse sources at catchment scale such as the hydrological simulation program-FORTRAN (HSPF) [35], agricultural nonpoint source pollution model (AGNPS) [36], pollution load (PLOAD) [37], soil and water assessment tool (SWAT) [38], and storm water management model (SWMM) [25]. However, most of the models developed so far are complex and require a large number of data, and hence are not feasible for data-scarce areas like Ethiopia.…”
Section: Watershed Model Selectionmentioning
confidence: 99%
“…Albek et al (2019) used the HSPF to assess the inflow impacts in the Sarısu catchment under climate change scenarios. The application of the HSPF in China (e.g., Li et al, 2017) and the USA (e.g., Ouyang et al, 2015) has also been reported.…”
Section: Methodsmentioning
confidence: 98%
“…The Nash‐Sutcliffe efficiency (NSE) (Nash and Sutcliffe ) is the most widely used indicator in hydrology because of its flexibility to apply to different types of mathematical models and intuitive interpretability (McCuen, Knight, & Cutter, ; Ritter & Muñoz‐Carpena, ; Schaefli & Gupta, ). It has been used widely in streamflow and run‐off predictions (Criss & Winston, ; Krause, Boyle, & Bäse, ; Li, Luo, Jiang, Wan, & Li, ; Moriasi et al, ; Noh et al, ; Schaefli & Gupta, ). It is a normalized measure comparing the mean square error generated by a model simulation to the variance of the observed values.…”
Section: Technical Methodsmentioning
confidence: 99%